Comparison of Surgical Procedures for Evacuating Uterus in The First Trimester Abortion - ramadan, Lena (Latakia University Journal -Medical Sciences Series, 2020)
Abortion is the Most Common Complication of Early Pregnancy, so that should be Effectively Managed with Safe and Appropriate Procedures. Surgical Evacuation of the Uterus for Management of First Trimester Abortions Usually Involves Electric Vacuum Aspiration (EVA) or Dilation and Curettage (D&C). Objective : to Detect the Method that Ensure more Safety and Efficacy for the First Trimester Abortion (EVA or D&C). The Study Included 100 Pregnant Women, Gestational Age Less than 12 Weeks, with Incomplete Abortion, Missed Abortion or Blighted Ovum, They were Allocated into two Groups, Group A (n=50) Underwent EVA, and Group B (n=50) Underwent D&C, The Procedures were Performed Using the General Anesthesia. Clinical Characteristics were Similar in the Two Groups, There were no Reports of Maternal Deaths, Cervical Laceration, Uterine Perforation, or Blood Transfusion Recorded in the two Groups. The Efficacy of EVA was the same as that of D&C in Successful the Procedure, but Pain and Blood Loss and Hospitalization were Experienced more in the D&C Group يعتبر الإسقاط هو الاختلاط الأكثر شيوعاً في مراحل الحمل المبكرة, لذلك كان لابد من اتباع طرق آمنة وفعالة لتدبيره. ويعتبر الإفراغ الجراحي إحدى الطرق المتبعة في تدبير إسقاطات الثلث الأول للحمل, وهذا يتضمن استخدام الرشف بالممص أو التوسيع والتجريف الآلي. يهدف البحث إلى تحديد الطريقة الأكثر أماناً وفعالية في تدبير إسقاطات الثلث الأول للحمل. أجريت الدراسة على 100 مريضة بقصة إسقاط ناقص أو منسي أو بيضة رائقة أو موت محصول حمل بعمر حملي ≥ 12 أسبوع حملي. قسمت المريضات إلى مجموعتين كل مجموعة 50 مريضة, تم تدبير مجموعة بالممص الكهربائي, ومجموعة بالتوسيع والتجريف الحاد تحت التخدير العام. كانت النتائج السريرية متشابهة بين مجموعتي الدراسة, ولم تسجل أي حالات وفاة أو انثقاب رحم أو تمزق رحم أو نزف غزير مهدد للحياة. كانت فعالية الرشف بالممص الكهربائي تماثل فعالية التجريف الحاد من حيث نجاح الإجراء في تدبير الإسقاط, ولكن الألم وخسارة الدم كانت أكبر في مجموعة التجريف الحاد.